2007
DOI: 10.1303/aez.2007.637
|View full text |Cite
|
Sign up to set email alerts
|

Possible function of Piezodorus hybneri (Heteroptera: Pentatomidae) male pheromone: Effects of adult age and diapause on sexual maturity and pheromone production

Abstract: To estimate the biological function of the male-produced pheromone of Piezodorus hybneri, we investigated the relationship between sexual maturity and pheromone production. Copulation was first observed at day 4 after emergence of males. The males showed high mating activity between days 5 and 15. Development of the ectodermal accessory gland (EAG) was also investigated as an indicator of male sexual maturity. The EAG, which was entirely immature at adult emergence, developed gradually between days 3 and 10. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…The present study clarified that diapausing males of R. pedestris with immature EFRs did not have pheromone components at all, while non-diapausing males with mature EFRs had pheromone components. A similar phenomenon in which diapausing males did not attract conspecific individuals and/or did not have pheromone components has been reported in P. hybneri (Endo et al, 2007) and E. lewisi (Takita, 2007), indicating that the profile of pheromone contents could be used as a criterion to define the status of male reproductive diapause in these bugs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The present study clarified that diapausing males of R. pedestris with immature EFRs did not have pheromone components at all, while non-diapausing males with mature EFRs had pheromone components. A similar phenomenon in which diapausing males did not attract conspecific individuals and/or did not have pheromone components has been reported in P. hybneri (Endo et al, 2007) and E. lewisi (Takita, 2007), indicating that the profile of pheromone contents could be used as a criterion to define the status of male reproductive diapause in these bugs.…”
Section: Discussionsupporting
confidence: 67%
“…In Eysarcoris lewisi (Heteroptera: Pentatomidae), males reared in the short photoperiod (8L16D) did not attract conspecific adults and nymphs (Takita, 2007). In Piezodorus hybneri (Heteroptera: Pentatomidae), no pheromone components were detected in any diapause males reared in the short photoperiod (12L12D) (Endo et al, 2007). In the southern green stink bug N. viridula, only sexually mature non-diapausing males attracted conspecifics, and diapausing females lacked the response to the male pheromone (Brennan et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…In adult males, the development of the ectodermal accessory gland has been used as an index of whether males had experienced diapause in this (Tachibana and Watanabe, 2007) as well as other heteropteran species: P. stali (Kotaki and Yagi, 1989), R. pedestris (ϭclavatus) (Numata and Kobayashi, 1989), and P. hybneri (Endo et al, 2007). In our study, the size of the ectodermal accessory gland was graded into: I: no enlargement observed, II: beginning to enlarge, III: full enlargement in the abdominal cavity, IV: full enlargement, and fluid accumulation.…”
Section: Methodsmentioning
confidence: 99%
“…Mizutani et al (2007) showed that there was individual variation in R. pedestris males in their attractiveness to the same species, and in the amount of pheromone produced. Endo et al (2007) revealed that adult age and reproductive diapause affect the production of pheromone components in P. hybneri males. In our study, we used a synthetic attractant to bait the traps and the sweeping method to monitor the seasonal occurrences of L. chinensis, and did not use male or female adults as attractants.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…Its effects seem to be related to sexual behavior, because males produce the pheromone only after sexual maturity, and no pheromone components were detected in diapausing males (Endo et al 2007). Higuchi (1999) reported that live males attracted not only conspeciÞc females, but also males, and Leal et al (1998) showed that the synthetic pheromone stimulates both sexes under laboratory conditions.…”
mentioning
confidence: 99%